The Policy of the Government of the Republic of Lithuania with Respect to Lithuanian Population in the Nazi Germany Occupied Klaipėda Region - Grybkauskas, Saulius (Genocidas ir rezistencija, 1998)
This article discusses the situation of Klaipėda region after its annexation to Nazi Germany, the problems faced by local Lithuanians, the measures taken by the Lithuanian government to protect Lithuanians from German repression, and German policy in the region.